A BERT-Based Classification Model: The Case of Russian Fairy Tales - Валерий Дмитриевич Соловьев; Марина Ивановна Солнышкина; Andrey Ten; Николай Аркадиевич Прокопьев (Journal of Language and Education)
Introduction: Automatic profiling and genre classification are crucial for text suitability assessment and as such have been in high demand in education, information retrieval, sentiment analysis, and machine translation for over a decade. Of all kinds of genres, fairy tales make one of the most challenging and valuable objects of study due to its heterogeneity and a wide range of implicit idiosyncrasies. Traditional classification methods including stylometric and parametric algorithms, however, are not only labour-intensive and time-consuming, but they are also struggling with identifying corresponding classifying discriminants. The research in the area is scarce, their findings are still controversial and debatable.